Management of upper urinary tract urothelial carcinoma. Issue 12 (December 2010) - Sun, Maxine; Abdo, Al''a; Abdollah, Firas; Schmitges, Jan; Thuret, Rodolphe; Jeldres, Claudio; Shariat, Shahrokh F; Perrotte, Paul; Karakiewicz, Pierre I
Upper urinary tract urothelial carcinoma (UTUC) is relatively uncommon. In this article, we review prognostic factors, criteria and indications for treatment with the available modalities using contemporary data. A systematic search on PubMed was performed using the keywords 'upper tract urothelial carcinoma'', ''upper tract transitional cell carcinoma'', ''nephroureterectomy'', 'laparoscopic'', 'endoscopic'' and 'prognostic factor''. The literature on UTUC is scarce. No prognostic factors have been formally validated in either the diagnosis or treatment of UTUC. The gold-standard management for invasive UTUC is radical nephroureterectomy with a bladder-cuff excision. Laparoscopic and endoscopic approaches represent alternatives in properly selected individuals. Segmental ureterectomy may also be considered. The extent and role of lymph node dissection remains to be validated. Chemotherapy may also be considered in select patients. Additional multi-institutional studies are needed to identify and validate prognostic factors that can predict the outcomes of patients diagnosed with UTUC. Randomized controlled trials are needed to assess the efficacy of the treatment modalities.